Reference values for fetal aortic isthmus blood flow parameters at 24 to 38weeks' gestation - Sornlada Thanasuan (2018)
Objective: The goal of this study is to establish population-specific nomograms of fetal aortic isthmus (AoI) Doppler indices in the period of 24-38weeks' gestation. Methods: This was a cross-sectional study of 240 Asian singleton pregnant women at 24-38 completed weeks' gestation. Fetal AoI blood flow was evaluated by Doppler study with automatic calculation of pulsatility index, resistance index, peak systolic velocity, end-diastolic velocity, and time-averaged maximum velocity. The relationship of these indices and gestational age was estimated by using regression analysis, and the best predictive models were determined to define mean, 5th, and 95th centile of each gestational age. The reproducibility was expressed by intraclass correlation coefficients and limits of agreement. Results: The mean maternal age was 28±5.7years. A total of 97% of all attempts to obtain AoI Doppler waveforms were successful with high interobserver and intraobserver reproducibility. Pulsatility index and peak systolic velocity significantly correlated with gestational age (P=0.03 and 0.001, respectively), whereas no significant change of resistance index, end-diastolic velocity, and time-averaged maximum velocity with advancing gestation was observed. Conclusion: This study offers normative values of fetal AoI Doppler indices, which may be useful in the difficult task of fetal surveillance in growth-restricted fetuses among our population. © 2013 John Wiley & Sons, Ltd.